Exploring the connection between childhood trauma, dissociation, and borderline personality disorder in forensic psychiatry: a comprehensive case study - Scognamiglio, Claudia; Sorge, Antonia; Borrelli, Giovanni; Perrella, Raffaella; Saita, Emanuela (Frontiers in Psychology, 2024)
This case study examines the complex relationship between childhood trauma, dissociation, and Borderline Personality Disorder (BPD) within the context of forensic psychiatry. It focuses on a young murder defendant named "Paul", who has experienced various traumatic events, including childhood maltreatment and domestic violence. These experiences have led to dissociative states marked by high emotional intensity, particularly of an aggressive nature, and impaired impulse control, resulting in violent behavior during dissociative episodes. The study employs advanced assessment tools like Raven's Standard Progressive Matrices (SPM), the Millon Clinical Multiaxial Inventory-III (MCMI-III), and the Level of Service/Case Management Inventory (LS/CMI) to gain a comprehensive understanding of Paul's psychopathological condition, risk factors, and rehabilitation needs. The LS/CMI assessment highlights a high risk of recidivism, mainly influenced by family relationships, educational challenges, interpersonal connections, and aggressive tendencies. To address the multifaceted needs of individuals like Paul, the study emphasizes the importance of using transdiagnostic models for trauma and dissociation. This approach informs tailored treatment programs that include processing past traumatic experiences, improving self-identity, nurturing healthy relational patterns, and enhancing emotional regulation. Although this study is based on a single case, it serves as a model for integrating assessment tools and theoretical-clinical models in the field of forensic psychiatry. Understanding the intricate dynamics of childhood trauma, dissociation, and BPD is crucial for making informed decisions, conducting risk assessments, and developing rehabilitation programs within the justice system. Future research should expand the scope of cases and further validate assessment tools to advance our understanding of this complex relationship.